The Influence of Leadership and Organizational Culture on Organizational Commitment To Employees of Grand Mode Cendrawasih - Nurfatwa Andriani Yasin; Muhammad Nasir; Kurniawaty Kurniawaty (Economos : Jurnal Ekonomi dan Bisnis, 2023)
An organization needs a leader who can bring the company or organization to maintain consistency and be able to compete in the business world. This study aims to examine the influence of leadership and organizational culture on organizational commitment in 300 employees of Grand Mode Makassar consisting of staff, security and employees. The analysis method used in this study is multiple linear regression analysis with the help of SPSS. 14. This study found that there is a positive and significant influence between leadership on organizational commitment, and there is a positive and significant influence between organizational culture on organizational commitment. This research found that leadership is believed to be a major force or key driving an organization to build a new culture that must be adjusted to change, and organizational culture is very influential on employee behavior because the value system in organizational culture can be used as a reference for behavior in organizations that are oriented towards achieving goals or performance results set.